Urgency of Civic Education in the Global Context (Human Rights) in South Africa and Hong Kong - Febi Fadilah (Journal of Moral and Civic Education)
Citizenship education exists because the problems that occur in society. The urgency of citizenship education is very important due to global issue of human rights that occur in South Africa and Hong Kong. The purpose of this article is to show how we can see the urgency of citizenship education in the context of global issues (Human Rights) in South Africa and Hong Kong both theoretically and factually. This research uses descriptive qualitative method by seeking some information from 15 national indexed journal, documentation and some other sources that support the research objectives and metaanalysing to get critical and valid research. The results of this study says that citizenship education has an important role viewed by historically and empirically in minimizing human rights issues, society have an erudation of their country and participate in understanding of universal citizenship to face global challenges.